2008
DOI: 10.1126/science.1158954
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Impulse on the Initiation of Particle Movement Under Turbulent Flow Conditions

Abstract: Fundamental to our understanding of erosional and transport phenomena in earth-surface dynamics and engineering is knowledge of the conditions under which sediment motion will begin when subjected to turbulent flow. The onset criterion currently in use emphasizes the time-averaged boundary shear stress and therefore is incapable of accounting for the fluctuating forces encountered in turbulent flows. We have validated through laboratory experiments and analytical formulation of the problem a criterion based up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
267
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 296 publications
(291 citation statements)
references
References 20 publications
10
267
0
Order By: Relevance
“…This makes it of even greater utility and urgency to identify relevant criteria, which can be used and associated to riverbank stability. Further analysis using recently suggested event-based criteria for sediment transport, which appropriately accounts for the scales of coherent turbulent flow structures [53,54] and relevant modelling tools [24,25,55], would be also relevant to pursue in future studies. Such efforts should focus on investigating the potential of such criteria to better characterize the erosive capacity of flow turbulence on riverbanks, and find practical applications on vegetation flow hydrodynamics, engineering ecohydraulics and fluvial geomorphology.…”
Section: Implications For Riverbank Stabilitymentioning
confidence: 99%
“…This makes it of even greater utility and urgency to identify relevant criteria, which can be used and associated to riverbank stability. Further analysis using recently suggested event-based criteria for sediment transport, which appropriately accounts for the scales of coherent turbulent flow structures [53,54] and relevant modelling tools [24,25,55], would be also relevant to pursue in future studies. Such efforts should focus on investigating the potential of such criteria to better characterize the erosive capacity of flow turbulence on riverbanks, and find practical applications on vegetation flow hydrodynamics, engineering ecohydraulics and fluvial geomorphology.…”
Section: Implications For Riverbank Stabilitymentioning
confidence: 99%
“…Note that some alternative studies have suggested that the governing variable to determine the critical condition for entrainment of a particle by a turbulent flow is an impulse rather than a force [20]. Here, where a laminar flow condition is present, the classical force approach can be reasonably kept nevertheless.…”
Section: Analysis a Onset Of Granular Erosionmentioning
confidence: 99%
“…A recent study examined this phenomenon further under well controlled laboratory conditions and demonstrated that it is not the magnitude of the applied force alone that serves as the necessary and sufficient condition for particle entrainment but rather the combination of force and duration, or impulse. 25 The implication here is that the turbulence induced momentary peak forces acting on the bed material must last long enough to cause entrainment. Although results reported by Diplas et al 25 represent the behavior of a test particle in a well controlled environment, this conclusion implies that the impulse potential of a turbulent stream is relevant to the inception of bed material motion, rather than simply the magnitude of the instantaneous forces or timespace-averaged bed shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…25 The implication here is that the turbulence induced momentary peak forces acting on the bed material must last long enough to cause entrainment. Although results reported by Diplas et al 25 represent the behavior of a test particle in a well controlled environment, this conclusion implies that the impulse potential of a turbulent stream is relevant to the inception of bed material motion, rather than simply the magnitude of the instantaneous forces or timespace-averaged bed shear stress.…”
Section: Introductionmentioning
confidence: 99%